Pengaruh Kompetensi dan Motivasi terhadap Kinerja Karyawan DPH PT. Bio Farma (Persero) - Rizqia, Dinda Nurul; Nurani, Nina (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Employe performance is a major factor in achieving company goals and even company performance, this study aims to determine the partial effect of competence and motivation on the performance of DPH employees in the Cisarua Regional Office. This study uses a quantitative verification approach with interview techniques and questionnaires in data collection. The sample of this research is probability sampling which is a sampling technique by providing equal opportunities for each population. Data analysis uses simple liner regression techniques and multiple liner regeresi to assess the effect of independent variables on the dependent variable. The results showed that the competence and motivation of DPH employees in the Cisarua Regional Office The competence of employees can be said to be in a moderate or moderate category by showing a value of >0.67. However, partially competence and motivation have a positive and significant influence on the performance of DPH employees in the Cisarua Regional Office, with the percentage amount for the competency variable being 12.25% and motivation amounting to 11.2%. While simultaneously competence and motivation have a positive and significant effect on performance by 38%, then 62% is influenced by other variables outside this study.